An Investigation of the Physical Environment and Employee Performance toward Customer Satisfaction in the Luxury Hotel: A Study in Bandung, Indonesia - Nono Wibisono; Widi Senalasari; Martin Elliott-White (Journal of Marketing Innovation (JMI), 2022)
This study aims to investigate the relationships between physical environment and employee toward customer satisfaction in luxury-hotels (four-star) and enrich the hoteliers with insight on which attributes of physical environment and employee that are most crucial to increase the satisfaction. Using quantitative approach with a large-scale survey to explore customer satisfaction, data were collected through 300 questionnaires and distributed to guests of luxury hotels around Bandung with 260 questionnaires returned. To analyze the data, a simple regression analysis was run. The main finding showed that customer satisfaction could be explained by physical environment dimension, with the highest contribution came from hotel décor. However, the result also showed that the employee dimension could also explain customer satisfaction. In fact, employee has the strongest impact towards customer satisfaction compared to physical environment. As a conclusion, it can be said that while service constitutes tangible and intangible aspects, this research shows that the intangible aspect seems to play the more vital role in delivering service in the hospitality industry. This paper will help hoteliers of luxury-hotel to decide which factors they should consider the most to increase the satisfaction of their guests.